2006
DOI: 10.3892/or.15.2.401
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-induced cell growth arrest and partial differentiation is related to the suppression of Id1 in human hepatoma cells

Abstract: Abstract. Transforming growth factor beta 1 (TGF-ß1) is a proposed regulator of Ids (inhibitors of DNA binding/differentiation) gene expression in epithelial cells. We previously reported that Id proteins are variously expressed in human hepatocellular carcinomas (HCC). However, the mechanism of regulation of Ids in HCC remains obscure. Here, we examined the relationship between Id1 and TGF-ß1 in four HCC cell lines, and studied the changes in cell proliferation, cell cycle and differentiation. The four HCC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 25 publications
4
30
0
Order By: Relevance
“…We could demonstrate that IFN -2b or TGF 1 stimulations not only decreased cellular proliferation but also increased apoptotic cell death [142]. The apoptotic and anti-proliferative effects of both cytokines separately have already been reported in HepG2 and Huh7 [143][144][145]. More interestingly, we demonstrated that the combined treatment increased these effects.…”
Section: Studies In Hcc Cell Linessupporting
confidence: 66%
“…We could demonstrate that IFN -2b or TGF 1 stimulations not only decreased cellular proliferation but also increased apoptotic cell death [142]. The apoptotic and anti-proliferative effects of both cytokines separately have already been reported in HepG2 and Huh7 [143][144][145]. More interestingly, we demonstrated that the combined treatment increased these effects.…”
Section: Studies In Hcc Cell Linessupporting
confidence: 66%
“…With respect to studies concerning the G 1 /S transition, a role for TGF-β1 receptor signaling in a various cell types has been well documented. [54][55][56][57] These studies have established that a transitory arrest in cell proliferation occurs during G 1 /S phase transition. This delay appears to be mediated by the induced expression of cyclin-dependent kinase inhibitors (CKIs) such as p15 ink4b (p15), p21 cip1 (p21) and p27 kip1 (p27), 58 and by the down-regulation of a critical G 1 /S phosphatase Cdc25A.…”
Section: Discussionmentioning
confidence: 99%
“…The reason behind the discrepancy between the kinetics of Id1 mRNA and protein induction remains unknown at this stage, but it could be related to an altered stability of Id1 protein. It should be noted that several reports demonstrate a repression of Id1 expression by TGF-␤1 in different cells (33,34), suggesting that the response of Id1 expression to TGF-␤1 is dictated by the particular contents of the cells. Consistent with this notion, recent studies also indicate that TGF-␤1 induces Id1 expression in rat hepatic stellate cells and human fetal lung fibroblasts (35,36).…”
Section: Discussionmentioning
confidence: 99%